Ocular Syphilis as a Cause of Chronic Postoperative Uveitis Followed by a Localized Ocular Jarisch–Herxheimer-like Reaction. (16th March 2023) - Forouzan, Parsha; Fell, David; Jones, Freddie R.
ABSTRACT: Objective: The case draws attention to syphilis as a cause of chronic postoperative uveitis following cataract surgery and is the first to document transient worsening of ocular inflammation without systemic symptoms after initiation of treatment, suggesting a localized Jarisch–Herxheimer-like reaction. Design: Case report. Results: The average thickness of the retinal nerve fiber layer was used as an objective measure of intraocular inflammation. The patient's nerve edema worsened during a standard neurosyphilis treatment course and returned to normal several weeks after completion of therapy. Conclusion: Syphilis serologic testing should be strongly considered in the work-up for chronic postoperative uveitis. A localized ocular Jarisch–Herxheimer-like reaction may occur and should not detract from completion of neurosyphilis treatment.